Recruiting the Digital-Age Applicant: The Impact of Ophthalmology Residency Program Web Presence on Residency Recruitment - Goerlitz-Jessen, Mark; Behunin, Nicholas; Montijo, Maria; Wilkinson, Michael (Journal of Academic Ophthalmology, 2018)
Background The phenomenon of internet dependence has changed the way the rising generation seeks information. This mentality has caused medical students to turn to online resources as they seek information about potential residency training programs. Residency program web presence (PWP) is increasingly important, and may even impact recruitment efforts. Improvement of PWP could enhance programs' recruitment of ideal candidates.Objectives The purpose of this study is to assess how ophthalmology residency PWP is impacting the residency recruitment process by understanding how it influences applicants' application and rank list choices as well as to identify the contributing factors.Methods Applicants applying for ophthalmology residency training at Penn State University during the 2015–2016 and 2016–2017 application cycles were surveyed using Research Electronic Data Capture (REDCap). Surveys sought applicants' perspectives with respect to their experiences with PWP and how those experiences shaped their application and rank list decisions.Results Of 860 applicants, 214 (24.9%) responded, accounting for 17.4% (214/1,228) of all ophthalmology residency applicants during the respective cycles; 72.4% of respondents expressed PWP does impact where they apply, how they form their rank list, or both; 93.4% said websites are an important resource during the application process; 47.2% conveyed interest in programs utilizing social media tools; and 76.5% of respondents felt websites gave sufficient information less than 50% of the time.Conclusion Ophthalmology PWP does impact resident recruitment. By enhancing program websites and adding social media tools, programs can improve recruitment efforts.
Keywords: ophthalmology residency; website; social media; web presence; recruitment; residency application; residency match